2020
DOI: 10.3390/ijerph17072516
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis for Patient Safety in Surgical Departments: Cross-Sectional Design Usefulness

Abstract: (1) Background: Identifying and measuring adverse events (AE) is a priority for patient safety, which allows us to define and prioritise areas for improvement and evaluate and develop solutions to improve health care quality. The aim of this work was to determine the prevalence of AEs in surgical and medical-surgical departments and to know the health impact of these AEs. (2) Methods: A cross-sectional study determining the prevalence of AEs in surgical and medical-surgical departments was conducted and a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Although it is difficult to objectively investigate safety strategies due to the relative rarity of WSS events [ 1 ], studies and interviews have shown that marking the surgical site is an important building block and thus a crucial layer in the cheese model for preventing WSS [ 1 , 3 , 8 , 11 , 12 , 19 ]. There is thus a need for a safe, simple and unambiguous ENT labeling procedure [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is difficult to objectively investigate safety strategies due to the relative rarity of WSS events [ 1 ], studies and interviews have shown that marking the surgical site is an important building block and thus a crucial layer in the cheese model for preventing WSS [ 1 , 3 , 8 , 11 , 12 , 19 ]. There is thus a need for a safe, simple and unambiguous ENT labeling procedure [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified misreporting in the OR schedule as a source of error for WSSs [ 19 , 23 ]. The surest confirmation lies in reconciling multiple sources, especially the inclusion of the not-yet-sedated patient in combination with the admission/informed consent document [ 11 , 12 , 16 , 18 ]. Relying solely on the information provided by the patient or family members can also be a cause of WSS [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the need to prioritise improving the quality of care and guaranteeing patient safety, recent studies have focused on detecting, classifying and quantifying AEs to prevent them (Aranaz et al., 2020; Vincent & Amalberti, 2016). The surgical department is a unique setting with a high rate of risks associated with the activity, with a significantly higher prevalence of AEs compared to other departments, with half of the cases being avoidable (Aranaz et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical safety that was not implemented properly was influenced by various factors such as worked routines, tight operating schedules, busyness, and lack of personnel (Spagnolo et al 2013;WAPS 2009). Failure to practiced safe surgery could've result in some unwanted cases and could've result in disability and even death (Aranaz Ostáriz et al 2020).…”
Section: Introductionmentioning
confidence: 99%